The learning style USD1000 challenge: a review / Caroline Joseph … [et al.] - Joseph, Caroline; Baharum, Norzie Diana; Mustapha, Musramaini; Md Shah, Nursyaidatul Kamal (2014)
It is a norm that every opinion or theory has two sides of its coin; one that sings praises of its significance, and the other that tramples and undermines its existence. The learning styles too do not portray all-praises and significance alone. There have been many researches conducted related to debunking the myth of learning styles. Hence, this paper is interested to look into how learning styles are viewed as myth in the first place. Besides, researchers too are still negotiating with the fact that if learning styles have any crucial role in a successful classroom teaching and learning process. Thus, this paper acts as a review of the myth of learning styles and also some works that have been projected to debunk the myth for the betterment of classroom environment and learning.